2015
DOI: 10.1038/cddis.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-rP1 suppresses epithelial–mesenchymal transition and metastasis in colorectal cancer

Abstract: Epithelial–mesenchymal transition (EMT) was initially recognized during organogenesis and has recently been reported to be involved in promoting cancer invasion and metastasis. Cooperation of transforming growth factor-β (TGF-β) and other signaling pathways, such as Ras and Wnt, is essential to inducing EMT, but the molecular mechanisms remain to be fully determined. Here, we reported that insulin-like growth factor binding protein-related protein 1 (IGFBP-rP1), a potential tumor suppressor, controls EMT in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Established regulators of EMT, such as SNAI1 (SNAIL), FN1 (fibronectin), CDH2 (N-cadherin) and IGFBP3 (insulin-like growth factor binding protein 3) [ 38 , 39 ], were down-regulated by COX-1 knockdown. In contrast, the negative regulators of EMT promoting cell-cell adhesion, such as CDH1 (E-cadherin), EPCAM and OCLN (occludin) [ 38 ], and the IGFBP7 antagonist of IGFBPs [ 40 ], were significantly up-regulated in OV3/COX1KD cells (Figure 4A & 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Established regulators of EMT, such as SNAI1 (SNAIL), FN1 (fibronectin), CDH2 (N-cadherin) and IGFBP3 (insulin-like growth factor binding protein 3) [ 38 , 39 ], were down-regulated by COX-1 knockdown. In contrast, the negative regulators of EMT promoting cell-cell adhesion, such as CDH1 (E-cadherin), EPCAM and OCLN (occludin) [ 38 ], and the IGFBP7 antagonist of IGFBPs [ 40 ], were significantly up-regulated in OV3/COX1KD cells (Figure 4A & 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, a putative TGF-␤ target gene, IGFBP7, a novel tumor stroma marker of CAFs and endothelial cells, is also induced in the EMT-like phenotype of CRC cells [137]. Conversely, our laboratory first found that IGFBP7 could inhibit EMT and tumor metastasis by repressing TGF-beta-mediated EMT through the Smad signaling cascade in CRC cells [138]. IGFBP7 may have different roles in specific microenvironment.…”
Section: Microenvironmental Regulation Of Emtmentioning
confidence: 92%
“…Further investigations showed that the knockdown of ASB3 promoted cell proliferation, migration, and invasion in cultured CRC cells, whereas the overexpression of WT ASB3 inhibited cell proliferation, migration, and invasion in vitro and reduced tumorigenicity and hepatic metastasis of CRC xenografts in vivo. Furthermore, we found that overexpression of ASB3 inhibited EMT of CRC cells, characterized by up-regulating epithelial markers β-catenin and E-cadherin and down-regulating mesenchymal markers TCF8, N-cadherin, and vimentin [43, 44]. Conclusively, ASB3 exerts a tumor-suppressive role in the pathogenesis and progression of CRC.…”
Section: Discussionmentioning
confidence: 99%